2016
DOI: 10.3390/cli4030044
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Homogeneity Analysis of Precipitation in Iran

Abstract: Abstract:The main objective of this study is to examine trend and homogeneity through the analysis of rainfall variability patterns in Iran. The study presents a review on the application of homogeneity and seasonal time series analysis methods for forecasting rainfall variations. Trend and homogeneity methods are applied in the time series analysis from collecting rainfall data to evaluating results in climate studies. For the homogeneity analysis of monthly, seasonal and annual rainfall, homogeneity tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…Bonnin et al [60] suggested that for good quality data checks, it is important to ensure: (i) check for extreme values above threshold; (ii) a real-data-check of values among others; (iii) dataset trend analysis; and (iv) a study of cross correlation between the gauges. Data were checked for outliers, normality and homogeneity by using parametric and nonparametric tests [61,62]. Outliers were defined by values over M + 3SD (M is the mean and SD is standard deviation) and compared with values from other gauging stations.…”
Section: Datamentioning
confidence: 99%
“…Bonnin et al [60] suggested that for good quality data checks, it is important to ensure: (i) check for extreme values above threshold; (ii) a real-data-check of values among others; (iii) dataset trend analysis; and (iv) a study of cross correlation between the gauges. Data were checked for outliers, normality and homogeneity by using parametric and nonparametric tests [61,62]. Outliers were defined by values over M + 3SD (M is the mean and SD is standard deviation) and compared with values from other gauging stations.…”
Section: Datamentioning
confidence: 99%
“…The maximum annual precipitation occurs in the west coast of the Caspian Sea (over 1300 mm) and to a lower extent in some parts of Zagros mountain range (~700 mm) [10], while the lowest amount of precipitation occurs in the centre and southeast of Iran (less than 100 mm) [11]. Numerous studies have been done on spatial and temporal variations of precipitation in Iran including [6,7,9,[12][13][14][15][16][17]. But few of these studies [6,18] focus on the moisture sources of Iran's precipitation due to the complexity of moisture sources identification, the lack of precise equipment and monitoring systems, and reliable sets of data.…”
Section: Introductionmentioning
confidence: 99%
“…This test is widely used in the climatological research especially for precipitation and temperature analysis [20][21][22]. We searched for temporal occurrence of discontinuities, so in each grid with a discontinuity, we looked for the year of its occurrence, and we were able to detect the discontinuity occurrence in a certain year.…”
Section: Methodsmentioning
confidence: 99%